Flotar y hundirse - Nelson, Robin, 1971- (Minneapolis : Ediciones Lerner, 2008)
An introduction to the difference between floating and sinking.
Includes index.
Accelerated Reader
Text in Spanish.
Keywords: Floating bodies -- Juvenile literature